PROFIL PENGETAHUAN NUMERASI MAHASISWA CALON GURU MATEMATIKA [PROFILE OF PROSPECTIVE MATHEMATICS TEACHERS’ NUMERACY KNOWLEDGE] - Melissa, Margaretha Madha; Kristanto, Yosep Dwi (Universitas Pelita Harapan, 2024)
The 21st-century skills that students and teachers must have are literacy skills, learning skills and life skills. One of the literacy skills is mathematical literacy, also known as numeracy. This research aims to describe the numeracy knowledge profile of prospective mathematics teacher students. This type of research is quantitative descriptive research. The subjects of this research were 32 prospective mathematics teacher students at a private university in Yogyakarta. Data collection techniques in this research used questionnaires and interviews. The research results show that the majority of prospective mathematics teacher students are doubtful about their knowledge of numeracy. Furthermore, none of the students mentioned the complete meaning of numeracy skills; most only mentioned numeration as numbers and mathematical symbols, solving everyday problems, and number operations. Students are also unable to mention the content and context of numeracy questions. However, all students realize that as prospective mathematics teachers, it is important to study numeracy and implement it in the classroom. The suggestion to improve numeracy knowledge and skills are through lesson study that focuses on numeracy to introduce numeracy practices and as a model for prospective teachers, as well as using a student-centered learning approach, using real problems such as RME.BAHASA INDONESIA ABSTRACT: Kemampuan abad ke-21 yang perlu dimiliki oleh siswa dan guru adalah kemampuan literasi, kemampuan belajar, dan kemampuan hidup. Salah satu kemampuan literasi adalah literasi matematika atau juga dikenal dengan istilah numerasi. Tujuan penelitian ini adalah untuk mendeskripsikan profil pengetahuan numerasi mahasiswa calon guru matematika. Jenis penelitian ini adalah penelitian deskriptif kuantitatif. Subjek penelitian ini adalah 32 mahasiswa calon guru matematika di salah satu universitas swasta di Yogyakarta. Teknik pengambilan data dalam penelitian ini menggunakan kuesioner dan wawancara. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa calon guru matematika ragu-ragu akan pengetahuan mereka tentang numerasi. Selain itu, tidak ada mahasiswa yang menyebutkan pengertian numerasi dengan lengkap, sebagian besar hanya menyebutkan numerasi sebagai angka dan simbol matematika, memecahkan masalah sehari-hari, dan operasi bilangan. Mahasiswa juga tidak mampu menyebutkan konten dan konteks soal numerasi. Walaupun demikian, semua mahasiswa menyadari sebagai calon guru matematika penting untuk mempelajari numerasi dan mengimplementasikannya di kelas. Hal yang bisa dilakukan untuk meningkatkan pengetahuan dan kemampuan numerasi yaitu melalui lesson study yang berfokus pada numerasi untuk mengenalkan praktik numerasi dan sebagai model bagi calon guru, serta menggunakan pendekatan pembelajaran yang berpusat pada siswa, menggunakan permasalahan nyata seperti PMR.